Distinguishing Maternity Shoots on Instagram: Capital, Class, Field - Dolorosa, Gloria Natalia (KnE Social Sciences, 2019)
This study is aimed at analyzing maternity shoots as a lifestyle habit and its relation with social class. Lifestyle is manifested in tastes, philosophical and morality beliefs, aesthetic tastes, clothes and cultures which become characteristics of a class. Meanwhile, cultural consumption expenditure signifies social classes. This study found that there are efforts to distinguish one’s status from other classes through maternity shoot practice, as part of power strategy. There are two classes studied in this research, namely petite-bourgeoisie and popular class, both of which seek to embrace the dominant class’ culture. By dispensing economic and cultural capital in Instagram as its field, the petite-bourgeoisie show how they are able to reap profits in form of positive appreciation and symbolic capital. Meanwhile, the popular class fails to achieve the same success in the Instagram field, marked by minimum appreciation toward their pictures. Nevertheless, bodies of pregnant women within the two classes have been subdued by Instagram convention as a game arena. The study also tested specific practices of pregnant women to represent their self-identity. Using consumer culture theory, it can be seen how pregnant women spend capital to establish their self-identity as a perfect woman, perfected by their pregnancy. Keywords: pregnant, Instagram, capital, social classes, Bourdieu.